Vitamin C and Cancer: What can we Conclude - 1,609 Patients and 33 Years Later: comment on the article by Cabanillas - Saul, Andrew W.; Jorge Duconge, Michael J. González Jorge R. Miranda-Massari,; Fernando Cabanillas, Reply by (Puerto Rico Health Sciences Journal, 2010)
bcb